HOW COVID-19 OUTBREAK PANDEMIC PROVOKES INDUSTRIAL ACTIVITY ALTERATION IN KARAWANG - Aina Nindiani; Afif Hakim; Dicky Suryapranatha; Aris Insan Waluya; Amelia Nur Fariza (Industry Xplore, 2021)
In early 2020, COVID-19 was present and changed the socio-economic order of the community. All sectors were affected as well as industrial sectors for both manufacturing and services. The business' operation has changed to comply with health protocols to prevent the spread of the coronavirus. The impacts of the COVID-19 in the industry identified in this study were decreased income, supply chain disruption, the onset of free time at work, and implementation of health protocols. This impact caused changes in activities in the form of reduced working hours, reduction of workers, material and process efficiency, increased lead time and delays in distribution, physical distancing, activities to prevent exposure to COVID-19, disinfection activities in companies, early detection of COVID-19, and increased employee immunity. Strategies that can be carried out are building a commitment to maintaining discipline in implementing health protocols, utilizing digital technology (internet of things) to expand the market, and implementing a lean strategy to achieve efficiency or save resources.